hello this is my first post on this forum and i hope i am in the right category,
i have a two equations i just cant solve, so please,please,please help me.
(2x+3)/(x-1)=2+(5/(x-1))
x²-3x+1-(9/4)-3*(3/2)+1=(x-(3/2))²
HI
$\displaystyle \frac{2x+3}{x-1}=\frac{2(x-1)+5}{x-1}$
Multiply both sides by x-1
$\displaystyle 2x+3=2x-2+5$
Continue here .
(2) $\displaystyle x^2-3x+1-\frac{9}{4}-3(\frac{3}{2})+1=(x-\frac{3}{2})^2$
$\displaystyle x^2-3x+1-\frac{9}{4}-\frac{9}{2}+1=x^2-3x+\frac{9}{4}$
Multiply both sides by 4
$\displaystyle 4x^2-12x+4-9-18+4=4x^2-12x+9$
$\displaystyle -12x-23=-12x$
Are you sure this is the correct equation , or else any value of real x would satisfy .